TECHNOLOGY OF CLEANING LOW-POTENTIAL ARTESIAN WATERS OF NORTH DAGESTAN FROM TOXIC COMPOUNDS - A. G. Kaymarazov (Юг России: экология, развитие)
Annotation. The problems and technological solutions have been considered for the demineralization and cleaning of the low-potential artesian waters of North Dagestan, promising for using in the systems of geothermal hot water supply and as a source of drinking water. The proposed method allows the problem of single-stage cleaning waters from arsenic compounds and humic acids. This method has been tested on Dagestan artesian waters, which contained arsenic in an amount significantly exceeding a standard value for such pollutant.Abstract. This study is aimed at decision of important socio-economic problems, such as heat and water supply to the population of the arid zones of Northern Dagestan based on complex use of low-potential geothermal waters’ reserves. Arsenic compounds and humic acids was found in the most studied waters in amounts far exceeding World Health Organization (WHO) limiting rate for drinking water by spectral analysis methods (AAS, SPM). The sorbent based on DEAE-cellulose modified with Fe3+ ions was prepared and tested by us for cleaning of the waters containing the arsenic compounds in an amount of more than 700 mcg/dm3 and humic acids in an amount approximately equal to 200 mg/dm3. This method has been successfully applied for the demineralization and cleaning of artesian waters in Kizlyarskiy, Tarumovskiy and Babayurtovskiy areas of Dagestan Republic to produce pure water complied with drinking water quality specification. Further studies, in our opinion, should be carried out in two directions, namely, coverage of new adjacent territories to study the mineral composition and identification of pollutants of underground drinking water of the North Caucasus region of Russia, as well as the creation of new efficient methods of purification of artesian water with a wider range of their pollutants.